2006
DOI: 10.1021/jp061415v
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Dependent Conformational Relaxation of cis-1,3,5-Hexatriene

Abstract: Ultrafast transient absorption spectroscopy was used to study the conformational relaxation dynamics of 1,3,5-cis-hexatriene (Z-HT) produced in the photochemical ring-opening reaction of 1,3-cyclohexadiene (CHD) in methanol and n-propanol solvents. The results are compared with earlier investigations performed using cyclohexane and hexadecane solvents [Anderson, N. A.; Pullen, S. H.; Walker II, L. A.; Shiang, J. J.; Sension, R. J.; J. Phys. Chem. A 1998, 102, 10588-10598.]. The conformational relaxation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 67 publications
7
32
0
Order By: Relevance
“…where S † is the difference in entropy between the reactant and the transition state, H † is the enthalpy of activation, and κ is the Kramers coefficient accounting for the influence of the solvent on the rate. 27,30 Assuming that the influence of the solvent is similar for both channels (see below), the difference in the prefactor for the fast and slow components correlates with a difference in the entropy of activation. The two transition states for decay of the excited state will involve the C-H and C-CH 3 groups on the two sides of the active C α -C β bond to differing degrees, providing a mechanism for a change in the entropy of the transition state.…”
Section: Excited State Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…where S † is the difference in entropy between the reactant and the transition state, H † is the enthalpy of activation, and κ is the Kramers coefficient accounting for the influence of the solvent on the rate. 27,30 Assuming that the influence of the solvent is similar for both channels (see below), the difference in the prefactor for the fast and slow components correlates with a difference in the entropy of activation. The two transition states for decay of the excited state will involve the C-H and C-CH 3 groups on the two sides of the active C α -C β bond to differing degrees, providing a mechanism for a change in the entropy of the transition state.…”
Section: Excited State Barriersmentioning
confidence: 99%
“…In contrast, the ground state single-bond isomerization of cZt-hexatriene → tZt-hexatriene does not exhibit any significant evidence for a viscosity dependent extrinsic barrier for isomerization. 27 Nonetheless the solvent still influences the reaction rate and the barrier in ways that depend, not on macroscopic solvent properties such as the solvent shear viscosity, but on the molecular details of the solvent. Preliminary molecular dynamics simulations suggest that the barrier for the cZt → tZt isomerization is higher in the alkanes studied by Harris et al because the molecules pack tightly around the hexatriene molecule and hinder the barrier crossing.…”
Section: Dependence Of the Excited State Dynamics On The Solventmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported a detailed theoretical and experimental study of the photorearrangement of compounds I into the tricyclic ketones II. [12] From this study, it was concluded that, although there is a non-adiabatic pathway that starts on the 1 A C H T U N G T R E N N U N G (np*) potential energy surface (PES), the reaction product is formed through the Although a detailed mechanistic study of the transformation of 1 into 2 has not yet been performed, several theoretical and experimental studies on related systems (hexatrienes [15] and diarylethenes [16] ) have established that the conrotatory 6p electrocyclization is allowed under photochemical activation and that the reaction occurs in the singlet manifold. [17] In both reaction pathways, the strong solvent dependence of the photochemical reactions of PK adducts 1 can be explained by the assumption that the 6p electrocyclization to 2 takes place through the A C H T U N G T R E N N U N G (pp*) state and strongly favor the rearrangement to 3.…”
Section: Resultsmentioning
confidence: 99%
“…Since they are mostly endothermic, light may not only assist to activate the alkanes but also supply the necessary excess energy. The direct photolysis of 1,3-c in solution is well known to lead to a ring cleavage with formation of hexatriene [10][11][12][13][14][15] in high quantum yield (/ = 0.4) at k irr = 254 nm [11]:The photodehydrogenation to benzene (1) takes apparently place only in the gas phase [16,17] but has not yet been observed in solution. The photoisomerization has been suggested to lead only to hexatriene.…”
mentioning
confidence: 99%